Peningkatan Kompetensi Akuntansi Berbasis Digital untuk UMKM yang Lebih Maju - Novindi Kaviusca, Jeni; Imainul Aprilian, Rahil (Indonesian Journal of Dedication and Educations, 2024)
MSMEs experience problems, especially in recording their finances. Even though financial recording is the main thing for running a business in a sustainable manner. One of the MSMEs that is the focus of this digital-based community service initiative is the Batik Melayu Pinang Sirih MSME. This service activity is carried out using socialization and practical methods. The time for this activity is 1 (one) day on October 1 2023. This community service activity takes place at the Pasir Padi Beach Souvenir Shop, Pangkal Pinang, Bangka Belitung Islands Province. Implementation of service consists of 4 stages. The outcome of this community service activity is that the activity runs without obstacles and can improve the ability of MSMEs to carry out accurate financial records using the Buku Warung application.